The Commoditized Self: Interpersonal Communication in Tinder Online Dating Apps - Mashita Phitaloka Fandia Purwaningtyas; Syakira N. Maharani; Dian Arymami (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
Online dating apps have changed the way people build interpersonal communication, particularly in the way they present and disclose themselves online in order to search for a relationship. The characteristic of online dating apps has urged users to build a rather liquid relationship; hence the transformation of intimacy and user’s view of romance, sex, and relationship. In the frame of computer-mediated communication and social informatics, socio-cultural context plays a significant role in shaping the self-presentation and self-disclosure performed by people, in the relation to the dating culture in Indonesia. In the case of Indonesia, this phenomenon is considered unique since the socio-cultural context is rather seeing the ‘liquidity’ in modern romance as banality and condemning the practice as immoral. This research aims to analyze the Indonesian socio-cultural context in shaping people’s self-presentation and self-disclosure in interpersonal communication through online dating apps, particularly Tinder. This research is conducted by a new ethnography method, involving 20 informants who are Indonesian youth active users of online dating apps. The key findings in this research include the contestation between self-agency and self-commodification in the practice of using online dating apps, as well as the shaping of contemporary dating culture among Indonesian youth. Apparently, the contemporary dating culture in Indonesia, also constructed heavily by online dating apps, allows ones to gain sexual revolution in the process of commodifying themselves.